A Pipelined Architecture for Interatomic Interactions Computation Considering Atomic Distribution - Chengyang Han; Jifeng Luo; Yan Pei; Qianjian Xing; Feng Yu (IEEE Access)
Domain-specific computing architectures significantly enhance the scale and performance of scientific simulations. In molecular dynamics, optimization of interatomic interaction computations is crucial for simulation accuracy. However, current methods aimed at optimizing accuracy rely on predefined interaction pipelines whose static computational configurations often lead to compromised resource efficiency. To address the difficulty mentioned above in calculating interatomic forces, we propose a Distribution-Aware Pair-Interaction Calculation (DAPIC) architecture that dynamically senses atomic distribution and allocates computational resources adaptively. This DAPIC architecture assigns computational weights to critical pair-interactions, enhancing the accuracy of essential distance calculations. DAPIC integrates Taylor series-based interpolation with a dynamically reloadable lookup table, emphasizing high-impact interaction regions. The experimental results demonstrate that comparable computational accuracy is achieved with significantly reduced resource demands, alleviating performance bottlenecks in interatomic force calculations. Specifically, the DAPIC-based design reduced the cumulative interatomic force error per atom by 70.8% and mitigated the atomic position and velocity drift errors by 86.2% and 85.6%, respectively, compared with single-precision GROMACS simulations. In long-term energy conservation tests, the total energy fluctuations closely align with those observed in double-precision GROMACS, underscoring the effectiveness of the architecture in preserving simulation fidelity.